Mathematical modeling of local corrosion element in pipelines with galvanic couple operating in soil conditions - Stepova, O.V.; Parashchiyenko, I.M. (Геотехнічна механіка, 2016)
Solution of the problem of modeling electrochemical corrosion in the pipeline sector with cracked insulating coating under the effect of electrolytic medium aggressive towards the pipeline metal is presented in this paper. The problem boils down to determining a stationary electrolytic field which occurs in the pipeline sector (a) in the crack when galvanic macrocouple operates with anode and (b) under the pipeline insulating coating when galvanic macrocouple operates with cathode. The advantage of this model is its ability to predict corrosion of the pipeline on time, which is important for determining the residual life of the structure. Distribution of potential electric field is determined by solving of the Laplace two-dimensional differential equation with given boundary conditions hence helping to obtain functional dependencies for calculation of current density (corrosion rate) and operating electric the acting galvanic macrocouple "crack in the metal - metal under the insulation coating" Розв’язана задача моделювання електрохімічної корозії ділянки трубопроводу в тріщині ізоляційного покриття при дії агресивного по відношенню до металу трубопроводу електролітичного середовиша, котра зводиться до визначення стаціонарного електричного поля, що виникає при роботі гальванопари з анодом на ділянці трубопроводу в тріщині і катодом на ділянці трубопроводу під ізоляційним покриттям. Перевагою даної моделі є можливість прогнозування розвитку корозії трубопроводу за часом, що є важливим при визначенні залишкового ресурсу конструкції. Розподіл потенціалу електричного поля визначено шляхом розв’язання двохмірного диференціального рівняння Лапласа із заданими граничними умовами, що дозволило отримати функціональні залежності для розрахунків щільності струму (швидкості корозії) та електричного струму діючої гальванопари «метал в тріщині – метал під ізоляційним покриттям» Решена задача моделирования электрохимической коррозии участка трубопровода в трещине изоляционного покрытия под действием агрессивной по отношению к металлу трубопровода электролитической среды, которая сводится к определению стационарного электролитического поля, которое возникает при работе гальванопары с анодом на участке трубопровода в трещине и катодом на участке трубопровода под изоляционным покрытием. Преимуществом данной модели является возможность прогнозирования развития коррозии трубопровода со временем, что является важным при определении остаточного ресурса конструкции. Распределение потенциала электрического поля определено решением двухмерного дифференциального уравнения Лапласа с заданными граничными условиями, что позволило получить функциональные зависимости для расчетов плотностей тока (скорости коррозии) и электрического тока действующей гальванопары «металл в трещине – металл под изоляционным покрытием».